Combined Magnetostratigraphy From Three Localities of the Rainstorm Member of the Johnnie Formation in California and Nevada, United States Calibrated by Cyclostratigraphy: A 13 R/Ma Reversal Frequency for the Ediacaran - Kodama, Kenneth P. (Frontiers in Earth Science, 2021)
Abstract. A combined magnetostratigraphy for the Rainstorm Member of the Ediacaran Johnnie Formation was constructed using the sediment accumulation rates determined by rock magnetic cyclostratigraphy for three localities of the Rainstorm Member to provide a high resolution, time-calibrated record of geomagnetic field reversal frequency at a critical time period in Earth history. Two previously reported magnetostratigraphy records from Death Valley, California, the Nopah Range and Winters Pass Hills (Minguez et al., 2015), were combined with new paleomagnetic and cyclostratigraphic results from the Desert Range locality of the Rainstorm Member in south central Nevada, USA. The Johnnie oolite marker bed is at the base of each of the three sections and allows their regional correlation. The Nopah Range and Desert Range localities have similar sediment accumulation rates of ~ 5 cm/ka, so their stratigraphic sections can be combined directly. The Winters Pass Hills locality has a higher sediment accumulation rate of 8.4 cm/ka, therefore its stratigraphic positions are multiplied by 0.6 to combine with the Desert Range and Nopah Range magnetostratigraphy. The thermal demagnetization results from the Desert Range locality isolates characteristic remanent magnetizations that indicate two nearly antipodal east-west and shallow directions and a mean paleopole (11.7˚N, 348.4˚E) that is consistent with “shallow” Ediacaran directions. The Desert Range also yields a magnetic susceptibility rock magnetic cyclostratigraphy that records short eccentricity, obliquity, and precession astronomically-forced climate cycles in the Ediacaran. The high-resolution combined magnetostratigraphy with nearly meter-scale stratigraphic spacing (nominally 23 ka, based on the Desert Range sediment accumulation rate), indicates 11 polarity intervals in a cyclostratigraphy-calibrated duration of 849 ka, indicating a reversal frequency of 13 R/Ma. The Rainstorm Member records the Shuram carbon isotope excursion, hence its age is ~574 Ma. Given the recent cyclostratigraphy-calibrated reversal frequency of 20 R/Ma from the Zigan Formation (Levashova et al., 2021) at 547 Ma, our results show that reversal frequency was high but fluctuated during the Ediacaran.